Synthesis and characterization of the disubstituted indene derivative 3-benzyl-l-t-butylamine(dimethylsilyl)indene and its sandwich complex with dichlorotitanium - Kundu, Kalipada (Journal of the Bangladesh Chemical Society, 2012)
The synthesis of the disubstituted indene derivative 3-benzyl-1-t-butylamine(dimethylsilyl)-indene, 3-C6H5CH2-1-SiMe2(NHBut)-C9H6, 1 and its sandwich complex with dichlorotitanium, [h5-3-C6H5CH2-1-SiMe2(NHBut)-C9H5]2TiCl2 2, and their characterization using 1H, 13C & 29Si-NMR and mass spectroscopy have been described. DOI: http://dx.doi.org/10.3329/jbcs.v24i2.9700 Journal of Bangladesh Chemical Society, Vol. 24(2), 115-122, 2011